GaN-based LED epitaxial structure, preparation method thereof and GaN-based LED

CN122995361APending Publication Date: 2026-10-27JIANGXI ZHAO CHI SEMICON CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611098296.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-23
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0002]现有技术中,GaN基LED均是基于异质衬底外延生长,如蓝宝石、硅(Si)或碳化硅(SiC)等,这些衬底与GaN外延层之间均存在晶格失配和热失配,这导致GaN外延层的位错密度高

Benefits of technology

本发明一实施例中的GaN基LED外延结构中的缓冲层包括依次层叠于衬底上的下包覆层、Zn3N2层和上包覆层,下包覆层和上包覆层将Zn3N2层包覆,使得其无直接暴露的界面;下包覆层为AlN层和/或第一AlGaN层,上包覆层为GaN层和/或第二AlGaN层。基于上述的GaN基LED外延结构,一者,在缓冲层中引入了Zn3N2层,其与六方GaN的(0001)面呈3:1晶向匹配的近外延关系,从而大幅降低了晶格失配,提升了后续生长各层的晶体质量,同时Zn原子能与界面悬挂键形成稳定配位,形成浅能级施主缺陷,不引入深能级的非辐射复合中心,有效抑制了载流子的非辐射复合,有效提升了发光效率。二者,Zn3N2层具有极高的成核密度(≥1×1011cm-2),其与上包覆层结合,可显著细化晶粒,阻断穿透位错,进一步降低后续各层的缺陷密度,提升发光效率。三者,通过采用下包覆层、Zn3N2层、上包覆层的结构,可实现Zn3N2层的完全包覆,解决了Zn3N2层高温易分解、易氧化的问题,实现了其在后续高温生长过程中的稳定。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122995361A_ABST
    Figure CN122995361A_ABST
Patent Text Reader

Abstract

The application relates to the field of semiconductor photoelectric devices, and particularly discloses a GaN-based LED epitaxial structure, a preparation method thereof and a GaN-based LED. The GaN-based LED epitaxial structure comprises a substrate, a buffer layer, an N-type GaN layer, an active layer and a P-type GaN layer in sequence; the buffer layer comprises a lower cladding layer, a Zn3N2 layer and an upper cladding layer which are stacked on the substrate in sequence; the lower cladding layer and the upper cladding layer cladding the Zn3N2 layer so that the Zn3N2 layer has no directly exposed interface; the lower cladding layer is an AlN layer and / or a first AlGaN layer, and the upper cladding layer is a GaN layer and / or a second AlGaN layer. The application can improve the light-emitting efficiency of the GaN-based LED.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of semiconductor optoelectronic devices, and more particularly to a GaN-based LED epitaxial structure and its fabrication method, and a GaN-based LED. Background Technology

[0002] In existing technologies, GaN-based LEDs are all grown epitaxially on heterogeneous substrates, such as sapphire, silicon (Si), or silicon carbide (SiC). These substrates exhibit lattice and thermal mismatches with the GaN epitaxial layer, resulting in a high dislocation density in the GaN epitaxial layer. For example, the lattice mismatch between sapphire substrate and GaN is approximately 16%, the thermal expansion coefficient mismatch is approximately 54%, and the typical dislocation density is 102. 8 ~10 10 cm -2 The lattice mismatch between the Si substrate and GaN is approximately 17%, the thermal expansion coefficient mismatch is as high as approximately 116%, and the typical dislocation density is 102. 9 ~10 10 cm -2 These dislocations can form nonradiative recombination centers, leading to a significant decrease in internal quantum efficiency (IQE) and a decline in the luminous efficiency of LEDs.

[0003] Currently, the buffers used in existing technologies are generally AlN layers or low-temperature GaN layers (LT-GaN), but their dislocation suppression effect is limited, and the dislocation density of GaN epitaxial layers still reaches 10. 8 cm -2 This limitation prevents the use of some large-sized substrates and makes it difficult to meet the performance requirements of some high-end devices (such as Mini-LED and Micro-LED). Summary of the Invention

[0004] The technical problem to be solved by the present invention is to provide a GaN-based LED epitaxial structure and its preparation method, which can improve luminous efficiency.

[0005] Another technical problem that this invention aims to solve is to provide a GaN-based LED.

[0006] To address the aforementioned problems, this invention discloses a GaN-based LED epitaxial structure, comprising a substrate, a buffer layer, an N-type GaN layer, an active layer, and a P-type GaN layer sequentially stacked on the substrate. The buffer layer includes a lower cladding layer, a Zn3N2 layer and an upper cladding layer stacked sequentially on the substrate. The lower cladding layer and the upper cladding layer cover the Zn3N2 layer, so that it has no directly exposed interface. The lower cladding layer is an AlN layer and / or a first AlGaN layer, and the upper cladding layer is a GaN layer and / or a second AlGaN layer.

[0007] As an improvement to the above technical solution, the thickness of the lower coating layer is 2nm~15nm, the thickness of the Zn3N2 layer is 10nm~50nm, and the thickness of the upper coating layer is 5nm~20nm.

[0008] As an improvement to the above technical solution, the lower cladding layer is an AlN layer and the upper cladding layer is a GaN layer.

[0009] As an improvement to the above technical solution, the substrate is a silicon substrate or a sapphire substrate.

[0010] As an improvement to the above technical solution, the thickness of the N-type GaN layer is 2μm~4μm, and the Si doping concentration is 5×10⁻⁶. 18 cm -3 ~2×10 19 cm -3 ; The active layer comprises alternating layers of quantum wells and quantum barriers with a period number of 5 to 15. The quantum well layer is an InGaN layer with a thickness of 2 nm to 4 nm and an In content of 0.1 to 0.22%. The quantum barrier layer is a GaN barrier layer or an AlGaN barrier layer. The GaN barrier layer has a thickness of 10 nm to 16 nm, and the AlGaN barrier layer has a thickness of 8 nm to 12 nm and an Al content of 0.05 to 0.15%. The thickness of the p-type GaN layer is 100 nm to 200 nm, and its Mg doping concentration is 1 × 10⁻⁶. 19 cm -3 ~5×10 19 cm -3 .

[0011] As an improvement to the above technical solution, it also includes an undoped GaN layer, an N-type AlGaN layer, an electron blocking layer, and a contact layer; The undoped GaN layer is disposed between the buffer layer and the N-type GaN layer, and its thickness is 2μm~4μm; The N-type AlGaN layer is disposed between the N-type GaN layer and the active layer, with a thickness of 100 nm to 200 nm, an Al composition ratio of 0.1% to 0.2%, and a Si doping concentration of 2 × 10⁻⁶. 18 cm -3 ~5×10 18 cm -3 ; The electron blocking layer is disposed between the active layer and the p-type GaN layer. It is a p-type AlGaN layer with a thickness of 5 nm to 25 nm, an Al content of 0.05 to 0.25%, and a Mg doping concentration of 1 × 10⁻⁶. 18 cm -3~5×10 19 cm -3 ; The contact layer is disposed on the p-type GaN layer, and it is a Mg-doped GaN layer with a thickness of 10 nm to 30 nm and a Mg doping concentration of 5 × 10⁻⁶. 19 cm -3 ~5×10 20 cm -3 .

[0012] Accordingly, the present invention also discloses a method for preparing a GaN-based LED epitaxial structure, which includes: Provide substrate; A buffer layer, an N-type GaN layer, an active layer, and a P-type GaN layer are sequentially grown on the substrate. The buffer layer comprises a lower cladding layer, a Zn3N2 layer, and an upper cladding layer sequentially stacked on the substrate. The lower cladding layer and the upper cladding layer cover the Zn3N2 layer, so that there is no directly exposed interface. The growth temperature of the buffer layer is 400℃~700℃. The lower cladding layer is an AlN layer and / or a first AlGaN layer, and the upper cladding layer is a GaN layer and / or a second AlGaN layer.

[0013] As an improvement to the above technical solution, the growth temperature of the lower coating layer is 400℃~600℃, and the growth pressure is 50 torr~200 torr; and before growing the lower coating layer, the substrate is treated with NH3 or N2 to establish a nitrogen-saturated interface. The growth temperature of the Zn3N2 layer is 400℃~600℃, and the growth pressure is 50 torr~200 torr; the growth temperature of the upper coating layer is 400℃~600℃, and the growth pressure is 50 torr~200 torr. After the upper coating layer is grown, it is annealed in an NH3 atmosphere at 1000℃~1150℃ for 3min~10min. Furthermore, the growth temperature and growth pressure of the lower coating layer, the Zn3N2 layer, and the upper coating layer are the same.

[0014] As an improvement to the above technical solution, the flow rate of NH3 during the growth of the buffer layer is 40 slm to 60 slm. After the buffer layer has grown, NH3 is introduced during the heating process at a flow rate of 40 slm to 60 slm.

[0015] Accordingly, the present invention also discloses a GaN-based LED, which includes the above-described GaN-based LED epitaxial structure.

[0016] Implementing this invention has the following beneficial effects: In one embodiment of the present invention, the buffer layer in the GaN-based LED epitaxial structure comprises a lower cladding layer, a Zn3N2 layer, and an upper cladding layer sequentially stacked on a substrate. The lower and upper cladding layers cover the Zn3N2 layer, eliminating any directly exposed interfaces. The lower cladding layer is an AlN layer and / or a first AlGaN layer, and the upper cladding layer is a GaN layer and / or a second AlGaN layer. Based on the above GaN-based LED epitaxial structure, firstly, the introduction of a Zn3N2 layer into the buffer layer, which exhibits a near-epicentric relationship with the (0001) plane of hexagonal GaN in a 3:1 crystal orientation match, significantly reduces lattice mismatch and improves the crystal quality of subsequent grown layers. Simultaneously, Zn atoms can form stable coordination with interface dangling bonds, creating shallow-level donor defects and preventing the introduction of deep-level nonradiative recombination centers, effectively suppressing nonradiative recombination of charge carriers and significantly improving luminous efficiency. Secondly, the Zn3N2 layer has an extremely high nucleation density (≥1×10⁻⁶). 11 cm -2 The combination of the lower coating layer, Zn3N2 layer, and upper coating layer significantly refines the grains, blocks penetrating dislocations, further reduces the defect density of subsequent layers, and improves luminescence efficiency. By employing a structure of a lower coating layer, a Zn3N2 layer, and an upper coating layer, complete coverage of the Zn3N2 layer can be achieved, solving the problems of easy decomposition and oxidation of the Zn3N2 layer at high temperatures and ensuring its stability during subsequent high-temperature growth. Attached Figure Description

[0017] Figure 1 This is a schematic diagram of the structure of a GaN-based LED epitaxial structure in one embodiment of the present invention; Figure 2 This is a schematic diagram of the structure of a GaN-based LED epitaxial structure in another embodiment of the present invention; Figure 3 This is a flowchart of a method for preparing a GaN-based LED epitaxial structure according to an embodiment of the present invention; In this diagram, 100 is the substrate, 200 is the buffer layer, 210 is the lower cladding layer, 220 is the Zn3N2 layer, 230 is the upper cladding layer, 300 is the undoped GaN layer, 400 is the N-type GaN layer, 500 is the N-type AlGaN layer, 600 is the active layer, 700 is the electron blocking layer, 800 is the P-type GaN layer, and 900 is the contact layer. Detailed Implementation

[0018] To facilitate understanding of the present invention, it will be described in more detail below. However, it should be understood that the present invention can be implemented in many different forms and is not limited to the embodiments or examples described herein. Rather, these embodiments or examples are provided to make the disclosure of the present invention more thorough and complete.

[0019] Furthermore, the terms "first" and "second" are used for descriptive purposes only and should not be construed as indicating or implying relative importance or implicitly specifying the number of technical features indicated. Thus, a feature defined as "first" or "second" may explicitly or implicitly include one or more of the stated features. In the description of this invention, "a plurality of" means two or more, unless otherwise explicitly specified.

[0020] In this invention, terms such as "first aspect" and "second aspect" are used for descriptive purposes only and should not be construed as indicating or implying relative importance or quantity, nor should they be construed as implicitly indicating the importance or quantity of the indicated technical features.

[0021] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. The terminology used herein in the specification of this invention is for the purpose of describing particular embodiments or examples only and is not intended to limit the invention. The optional range of the term "and / or" as used herein includes any one of two or more of the related listed items, as well as any and all combinations of the related listed items, including any two related listed items, any more related listed items, or a combination of all related listed items.

[0022] Please see Figure 1 As a first aspect of the present invention, a GaN-based LED epitaxial structure is disclosed, comprising a substrate 100, and a buffer layer 200, an N-type GaN layer 400, an active layer 600, and a P-type GaN layer 800 sequentially stacked on the substrate 100. The buffer layer 200 comprises a lower cladding layer 210, a Zn3N2 layer 220, and an upper cladding layer 230 sequentially stacked on the substrate 100. The lower cladding layer 210 and the upper cladding layer 230 cover the Zn3N2 layer 220, so that it has no directly exposed interface. The lower cladding layer 210 is an AlN layer and / or a first AlGaN layer, and the upper cladding layer 230 is a GaN layer and / or a second AlGaN layer. Based on the aforementioned GaN-based LED epitaxial structure, firstly, a Zn3N2 layer 220 is introduced into the buffer layer 200. This Zn3N2 layer exhibits a near-epicentric relationship with the (0001) facet of the hexagonal GaN, exhibiting a 3:1 crystal orientation match. This significantly reduces lattice mismatch and improves the crystal quality of subsequent grown layers. Simultaneously, Zn atoms can form stable coordination with interface dangling bonds, creating shallow-level donor defects and preventing the introduction of deep-level nonradiative recombination centers. This effectively suppresses nonradiative recombination of charge carriers and significantly improves luminous efficiency. Secondly, the Zn3N2 layer 220 possesses an extremely high nucleation density (≥1×10⁻⁶). 11 cm -2The combination of the lower coating layer 210, the Zn3N2 layer 220, and the upper coating layer 230 significantly refines the grains, blocks penetrating dislocations, further reduces the defect density of subsequent layers, and improves luminescence efficiency. By employing a structure of lower coating layer 210, Zn3N2 layer 220, and upper coating layer 230, complete coating of Zn3N2 layer 220 can be achieved, solving the problems of easy decomposition and oxidation of Zn3N2 layer 220 at high temperatures and ensuring its stability during subsequent high-temperature growth.

[0023] Specifically, in some embodiments, the thickness of the lower cladding layer 210 is 2nm to 15nm. If its thickness is too small, it may lead to incomplete coverage of the Zn3N2 layer 220, posing a risk of decomposition; if its thickness is too large, it may introduce excessive stress, resulting in an increase in dislocation density. For example, the thickness of the lower cladding layer 210 is 3nm, 5nm, 7nm, 9nm, 11nm, or 13nm, but is not limited to these. Preferably, it is 5nm to 15nm, and more preferably, it is 5nm to 10nm.

[0024] Specifically, in some embodiments, the thickness of the Zn3N2 layer 220 is 10 nm to 50 nm. If its thickness is too small, the nucleation density is relatively low, making it difficult to effectively refine the grains; if its thickness is too large, it may not be fully coated, making it prone to decomposition or oxidation. For example, the thickness of the Zn3N2 layer 220 is 15 nm, 20 nm, 25 nm, 30 nm, 35 nm, 40 nm, or 45 nm, but is not limited to these. Preferably, it is 10 nm to 30 nm, and more preferably, it is 15 nm to 30 nm.

[0025] Specifically, in some embodiments, the thickness of the upper coating layer 230 is 5 nm to 20 nm. If its thickness is too small, it is difficult to form a continuous film, causing the Zn3N2 layer 220 to decompose or oxidize due to exposure; if its thickness is too large, the crystal quality is poor due to the low growth temperature, and new crystal defects are easily introduced. Exemplarily, the thickness of the upper coating layer 230 is 6 nm, 9 nm, 12 nm, 15 nm, or 18 nm, but is not limited to these. Preferably, it is 8 nm to 20 nm, and more preferably, it is 10 nm to 20 nm.

[0026] Specifically, the lower cladding layer 210 is an AlN layer, a first AlGaN layer, or a combination of both. The Al content in the first AlGaN layer is 0.3-0.5%. Preferably, in some embodiments, the lower cladding layer 210 is an AlN layer, which has a low dislocation density and strong thermal stability, thus better protecting the Zn3N2 layer 220 and further improving crystal quality.

[0027] Specifically, the upper cladding layer 230 is a GaN layer, a second AlGaN layer, or a combination of both. The Al content in the second AlGaN layer is 0.05~0.2%. Preferably, in some embodiments, the upper cladding layer 230 is a GaN layer, whose lattice constant is more compatible with the subsequently grown layers, and it can better refine the grain size.

[0028] Specifically, the substrate 100 is a heterogeneous substrate, which can be any one of a sapphire substrate, a silicon substrate, a silicon carbide substrate, or a gallium oxide substrate, but is not limited to these. Preferably, it is a sapphire substrate or a silicon substrate, which are low in cost and have mature processing technology. It should be noted that the buffer layer 200 of the present invention enables the growth of high-quality epitaxial structures on large-size sapphire substrates and silicon substrates, improving yield and uniformity.

[0029] Specifically, the thickness of the N-type GaN layer 400 is 2 μm to 4 μm, exemplarily 2.4 μm, 2.8 μm, 3.2 μm, 3.5 μm, 3.8 μm, or 3.9 μm, but not limited thereto. The doping element of the N-type GaN layer 400 is Si or Ge, but not limited thereto. Preferably, it is Si, and the Si doping concentration is 5 × 10⁻⁶. 18 cm -3 ~2×10 19 cm -3 For example, 6.5 × 10 18 cm -3 8×10 18 cm -3 9.5×10 18 cm -3 1×10 19 cm -3 Or 1.5×10 19 cm -3 However, it is not limited to this.

[0030] Specifically, the active layer 600 comprises alternating layers of quantum wells and quantum barrier layers, with a period number of 5 to 15, exemplarily 7, 9, 10, 12, or 14, but not limited thereto. The quantum well layer is an InGaN layer with a thickness of 2 nm to 4 nm, exemplarily 2.3 nm, 2.6 nm, 2.9 nm, 3.2 nm, 3.5 nm, or 3.8 nm, but not limited thereto. The In content in the quantum well layer is 0.1% to 0.22%, exemplarily 0.13%, 0.16%, 0.19%, or 0.21, but not limited thereto. The quantum barrier layer is a GaN barrier layer or an AlGaN barrier layer, with a GaN barrier layer thickness of 10 nm to 16 nm, exemplarily 11.5 nm, 13 nm, 14.5 nm, or 15 nm, but not limited thereto. The thickness of the AlGaN barrier layer is 8 nm to 12 nm, exemplarily 8.5 nm, 9 nm, 10 nm, 10.5 nm or 11 nm, but not limited thereto. The proportion of Al component in the AlGaN barrier layer is 0.05 to 0.15, exemplarily 0.07, 0.09, 0.11, 0.13 or 0.14, but not limited thereto.

[0031] Specifically, the thickness of the p-type GaN layer 800 is 100nm~200nm, exemplarily 110nm, 130nm, 150nm, 170nm or 190nm, but not limited to these. The doping element of the p-type GaN layer 800 is Mg, and its Mg doping concentration is 1×10⁻⁶. 19 cm -3 ~5×10 19 cm -3 For example, 1.5 × 10 19 cm -3 2×10 19 cm -3 2.5×10 19 cm -3 3×10 19 cm -3 3.5×10 19 cm -3 4×10 19 cm -3 Or 4.5×10 19 cm -3 However, it is not limited to this.

[0032] Preferably, please refer to Figure 2 In some embodiments, the GaN-based LED epitaxial structure further includes an undoped GaN layer 300, an N-type AlGaN layer 500, an electron blocking layer 700, and a contact layer 900.

[0033] Specifically, an undoped GaN layer 300 is disposed between the buffer layer 200 and the N-type GaN layer 400, which can further reduce the dislocation density and improve the luminous efficiency. The thickness of the undoped GaN layer 300 is 2 μm to 4 μm. More specifically, the undoped GaN layer includes a three-dimensional island layer and a two-dimensional merged layer stacked sequentially; the thickness of the three-dimensional island layer is 600 nm to 1000 nm, and the thickness of the two-dimensional merged layer is 1.4 μm to 3 μm.

[0034] Specifically, an N-type AlGaN layer 500 is disposed between the N-type GaN layer 400 and the active layer 600. This allows for effective electron expansion, reduces the rate at which electrons are injected into the active layer 600, and improves the recombination efficiency of electrons and holes in the active layer 600, thereby further enhancing luminous efficiency. Specifically, the thickness of the N-type AlGaN layer 500 is 100 nm to 200 nm, exemplarily 120 nm, 140 nm, 160 nm, or 180 nm, but not limited to these. The proportion of Al component in the N-type AlGaN layer 500 is 0.1% to 0.2%, exemplarily 0.12%, 0.14%, 0.16%, or 0.18, but not limited to these. The doping element in the N-type AlGaN layer 500 is Si or Ge, but not limited to these; preferably Si, and the Si doping concentration is 2 × 10⁻⁶. 18 cm -3 ~5×10 18 cm -3 For example, 2.5 × 10 18 cm -3 3×10 18 cm -3 3.5×10 18 cm -3 4×10 18 cm -3 Or 4.5×10 18 cm -3 However, it is not limited to this.

[0035] Specifically, an electron blocking layer 700 is disposed between the active layer 600 and the p-type GaN layer 800. It prevents electrons from leaking into the p-type GaN layer 800 and undergoing non-radiative recombination, thereby further improving luminous efficiency. The electron blocking layer 700 is a p-type AlGaN layer with a thickness of 5 nm to 25 nm, exemplarily 8 nm, 11 nm, 14 nm, 17 nm, 20 nm, or 23 nm, but not limited thereto. The Al content in the electron blocking layer 700 is 0.05 to 0.25%, exemplarily 0.09, 0.13, 0.17, 0.21, or 0.24, but not limited thereto. The p-type dopant in the electron blocking layer 700 is Mg, and the Mg doping concentration is 1 × 10⁻⁶. 18 cm -3 ~5×10 19 cm-3 For example, 3×10 18 cm -3 5×10 18 cm -3 7×10 18 cm -3 9×10 18 cm -3 1×10 19 cm -3 Or 3×10 19 cm -3 However, it is not limited to this.

[0036] Specifically, the contact layer 900 is disposed on the p-type GaN layer 800. It is a Mg-doped GaN layer with a thickness of 10 nm to 30 nm, exemplarily 14 nm, 18 nm, 22 nm, or 26 nm, but not limited thereto. The p-type dopant of the contact layer 900 is Mg, and the Mg doping concentration is 5 × 10⁻⁶. 19 cm -3 ~5×10 20 cm -3 For example, 6×10 19 cm -3 8.5×10 19 cm -3 1×10 20 cm -3 2.5×10 20 cm -3 3×10 20 cm -3 Or 4.5×10 20 cm -3 However, it is not limited to this.

[0037] Preferably, in some embodiments, the GaN-based LED epitaxial structure further includes a stress relief layer (not shown in the figure), a structure commonly found in the art, disposed between the N-type AlGaN layer 500 and the active layer 600. This stress relief layer can weaken the polarization effect in the active layer 600, further improving luminous efficiency. Specifically, the stress relief layer comprises alternating layers of InGaN and Si-doped GaN. The InGaN layer has an In content of 0.05–0.1% and a thickness of 3–5 nm; the Si-doped GaN layer has a thickness of 4–8 nm and a Si doping concentration of 5 × 10⁻⁶. 17 cm -3 ~1×10 18 cm -3 .

[0038] Please see Figure 3As a second aspect of the present invention, the present invention discloses a method for preparing a GaN-based LED epitaxial structure, which includes: S1: Provides a substrate; S2: A buffer layer, an N-type GaN layer, an active layer, and a P-type GaN layer are grown sequentially on the substrate; The buffer layer comprises a lower cladding layer, a Zn3N2 layer, and an upper cladding layer sequentially stacked on the substrate. The lower cladding layer and the upper cladding layer cover the Zn3N2 layer, so that there is no directly exposed interface. The growth temperature of the buffer layer is 400℃~700℃. The lower cladding layer is an AlN layer and / or a first AlGaN layer, and the upper cladding layer is a GaN layer and / or a second AlGaN layer.

[0039] Based on the above-mentioned method for fabricating GaN-based LED epitaxial structures, firstly, a Zn3N2 layer is introduced into the buffer layer. This Zn3N2 layer exhibits a near-epicentric relationship with the (0001) facet of hexagonal GaN, showing a 3:1 crystal orientation match, thus significantly reducing lattice mismatch and improving the crystal quality of subsequent grown layers. Simultaneously, Zn atoms can form stable coordination with interface dangling bonds, creating shallow-level donor defects and preventing the introduction of deep-level nonradiative recombination centers, effectively suppressing nonradiative recombination of charge carriers and significantly improving luminous efficiency. Secondly, the Zn3N2 layer possesses extremely high nucleation density (≥1×10⁻⁶). 11 cm -2 The combination of the lower coating layer, Zn3N2 layer, and upper coating layer significantly refines the grains, blocks through-dislocations, further reduces the defect density of subsequent layers, and improves luminescence efficiency. By employing a structure of a lower coating layer, a Zn3N2 layer, and an upper coating layer, complete coverage of the Zn3N2 layer can be achieved, solving the problems of easy decomposition and oxidation of the Zn3N2 layer at high temperatures and ensuring its stability during subsequent high-temperature growth. Furthermore, controlling the growth temperature of the buffer layer to 400℃~700℃ effectively prevents the decomposition of the Zn3N2 layer.

[0040] Specifically, in some implementations, step S2 includes: S21: Grow a buffer layer on the substrate; The buffer layer can be grown using MOCVD or MBE, but is not limited to these methods. Preferably, in some embodiments, the lower coating layer, the Zn3N2 layer, and the upper coating layer are grown sequentially by MOCVD to obtain the buffer layer. Specifically, the growth temperature of the lower coating layer, the Zn3N2 layer, and the upper coating layer is 400℃~700℃, preferably 400℃~600℃. The growth pressure of the lower coating layer, the Zn3N2 layer, and the upper coating layer is 50 torr~200 torr, preferably 100 torr~200 torr.

[0041] Preferably, in some embodiments, the growth temperature of the lower coating layer, the Zn3N2 layer, and the upper coating layer is the same, which is 400℃~600℃; the growth pressure of the three is also the same, which is 50 torr~200 torr. That is, there is no temperature change and no pressure change during the growth of the buffer layer, which further stabilizes the Zn3N2 layer.

[0042] Preferably, in some embodiments, the substrate is treated with NH3 or N2 before the lower coating layer is grown to establish a nitrogen-saturated interface. More specifically, NH3 at a flow rate of 40 slm to 50 slm is introduced, and the substrate is treated at 400°C to 700°C for 5 s to 20 s to establish a nitrogen-saturated interface. A nitrogen-saturated interface can further reduce the interface state density and improve luminous efficiency.

[0043] Preferably, in some embodiments, after the upper coating layer has grown, it is annealed at 1000°C to 1150°C for 3 to 10 minutes in an NH3 atmosphere; the annealing treatment can optimize the crystal quality of the upper coating layer, which can then be used as a nucleation layer to achieve a good transition with the subsequent grown layers.

[0044] Preferably, in some embodiments, the flow rate of NH3 during the growth of the buffer layer is 40 slm to 60 slm; after the buffer layer growth is completed, NH3 is introduced during the heating process at a flow rate of 40 slm to 60 slm. That is, the NH3 atmosphere is maintained during the growth of the buffer layer and the heating annealing process, which can further suppress the thermal decomposition of the Zn3N2 layer and the loss of interfacial nitrogen, ensuring the stability of the encapsulated structure in high-temperature processes.

[0045] S22: Growing an undoped GaN layer on the buffer layer; Specifically, undoped GaN layers can be grown using methods such as MOCVD, MBE, and HVPE, but are not limited to these. Preferably, in some embodiments, a three-dimensional island layer and a two-dimensional merged layer are grown sequentially by MOCVD; the growth temperature of the three-dimensional island layer is 950℃~1050℃, the growth pressure is 200 torr~500 torr, and the V / III ratio is 2000~3000. The growth temperature of the two-dimensional merged layer is 1100℃~1200℃, the growth pressure is 150 torr~250 torr, and the V / III ratio is 300~800.

[0046] S23: Growing an N-type GaN layer on an undoped GaN layer; Specifically, N-type GaN layers can be grown using methods such as MOCVD, MBE, and HVPE, but are not limited to these. Preferably, in some embodiments, N-type GaN layers are grown by MOCVD at a growth temperature of 1050℃~1100℃ and a growth pressure of 150 torr~250 torr.

[0047] S24: Growing an N-type AlGaN layer on an N-type GaN layer; Specifically, N-type AlGaN layers can be grown using methods such as MOCVD, MBE, and HVPE, but are not limited to these methods. Preferably, in some embodiments, N-type AlGaN layers are grown by MOCVD at a growth temperature of 1000℃~1050℃ and a growth pressure of 150 torr~250 torr.

[0048] S25: An active layer is grown on an N-type AlGaN layer; Specifically, in some embodiments, quantum well layers and quantum barrier layers are periodically grown by MOCVD until an active layer is obtained. The growth temperature of the quantum well layer is 750°C to 800°C, and the growth pressure is 200 torr to 300 torr. The growth temperature of the quantum barrier layer is 850°C to 900°C, and the growth pressure is 200 torr to 300 torr.

[0049] S26: An electron blocking layer is grown on the active layer; Specifically, electron blocking layers can be grown using methods such as MOCVD, MBE, and HVPE, but are not limited to these. Preferably, in some embodiments, a p-type AlGaN layer is grown by MOCVD as an electron blocking layer; the growth temperature is 850℃~1100℃, and the growth pressure is 150 torr~200 torr.

[0050] S27: Grow a P-type GaN layer on an electron blocking layer; Specifically, P-type GaN layers can be grown using methods such as MOCVD, MBE, and HVPE, but are not limited to these. Preferably, in some embodiments, the P-type GaN layer is grown by MOCVD at a growth temperature of 920°C to 970°C and a growth pressure of 150 torr to 250 torr.

[0051] S28: A contact layer is grown on a P-type GaN layer; Specifically, the contact layer can be grown using methods such as MOCVD, MBE, and HVPE, but is not limited to these. Preferably, in some embodiments, Mg-doped GaN is grown by MOCVD as the contact layer, with a growth temperature of 800℃~900℃ and a growth pressure of 150 torr~250 torr.

[0052] Preferably, in some embodiments, after the contact layer growth is completed, the resulting epitaxial structure is annealed in a N2 atmosphere at 720°C to 800°C for 5 min to 15 min.

[0053] Accordingly, as a third aspect of the present invention, a GaN-based LED is also disclosed, comprising the aforementioned GaN-based LED epitaxial structure. The buffer layer in this GaN-based LED epitaxial structure comprises a lower cladding layer, a Zn3N2 layer, and an upper cladding layer sequentially stacked on a substrate. The lower and upper cladding layers cover the Zn3N2 layer, eliminating any directly exposed interfaces. The lower cladding layer is an AlN layer and / or a first AlGaN layer, and the upper cladding layer is a GaN layer and / or a second AlGaN layer. Based on the aforementioned GaN-based LED, firstly, the introduction of a Zn3N2 layer into the buffer layer, which exhibits a near-epicentric relationship with the (0001) plane of hexagonal GaN in a 3:1 crystal orientation match, significantly reduces lattice mismatch and improves the crystal quality of subsequent grown layers. Simultaneously, Zn atoms can form stable coordination with interface dangling bonds, creating shallow-level donor defects and preventing the introduction of deep-level nonradiative recombination centers, effectively suppressing nonradiative recombination of charge carriers and significantly improving luminous efficiency. Both, the Zn3N2 layer has an extremely high nucleation density (≥1×10). 11 cm -2 The combination of the lower coating layer, Zn3N2 layer, and upper coating layer significantly refines the grains, blocks penetrating dislocations, further reduces the defect density of subsequent layers, and improves luminescence efficiency. By employing a structure of a lower coating layer, a Zn3N2 layer, and an upper coating layer, complete coverage of the Zn3N2 layer can be achieved, solving the problems of easy decomposition and oxidation of the Zn3N2 layer at high temperatures and ensuring its stability during subsequent high-temperature growth.

[0054] The present invention will be further described below with reference to specific embodiments: Example 1 This embodiment provides a GaN-based LED epitaxial structure, which includes a substrate, and a buffer layer, an undoped GaN layer, an N-type GaN layer, an N-type AlGaN layer, an active layer, an electron blocking layer, a P-type GaN layer, and a contact layer sequentially stacked on the substrate.

[0055] The substrate is a sapphire substrate. The buffer layer comprises a lower cladding layer, a Zn3N2 layer, and an upper cladding layer sequentially stacked on the substrate. The lower and upper cladding layers cover the Zn3N2 layer, eliminating any directly exposed interfaces. The lower cladding layer is a first AlGaN layer with an Al content of 0.45% and a thickness of 10 nm. The Zn3N2 layer has a thickness of 20 nm. The upper cladding layer is a second AlGaN layer with an Al content of 0.1% and a thickness of 18 nm.

[0056] The undoped GaN layer comprises sequentially stacked three-dimensional island layers and two-dimensional merged layered layers; the thickness of the three-dimensional island layers is 800 nm, and the thickness of the two-dimensional merged layered layers is 2 μm. The N-type GaN layer has a thickness of 3 μm and a Si doping concentration of 8 × 10⁻⁶. 18 cm -3The N-type AlGaN layer is 140 nm thick, with an Al content of 0.14% and a Si doping concentration of 2.5 × 10⁻⁶. 18 cm -3 The active layer consists of alternating layers of quantum wells and quantum barriers, with a period number of 8. The quantum well layers are of type In. 0.15 Ga 0.85 The N-layer is 3 nm thick, the quantum barrier layer is a GaN barrier layer with a thickness of 10 nm, and the electron blocking layer is a p-type AlGaN layer with a thickness of 20 nm. The Al composition is 0.15%, and the Mg doping concentration is 8.5 × 10⁻⁶. 18 cm -3 The thickness of the p-type GaN layer is 140 nm, and its Mg doping concentration is 4 × 10⁻⁶. 19 cm -3 The contact layer is a Mg-doped GaN layer with a thickness of 15 nm and a Mg doping concentration of 3.5 × 10⁻⁶. 20 cm -3 .

[0057] The method for fabricating the GaN-based LED epitaxial structure in this embodiment includes the following steps: (1) Provide a substrate; Specifically, the sapphire substrate was annealed at 1100°C for 5 minutes in an H2 atmosphere.

[0058] (2) A buffer layer is grown on the substrate; Specifically, the buffer layer is obtained by sequentially growing the lower coating layer, the Zn3N2 layer, and the upper coating layer using MOCVD.

[0059] Before the growth of the lower cladding layer, the substrate was treated with NH3 at a flow rate of 45 slm to establish a nitrogen-saturated interface. During the growth of the lower cladding layer, the NH3 flow rate was 50 slm, the growth temperature was 500℃, and the growth pressure was 100 torr.

[0060] During the growth of the Zn3N2 layer, the NH3 flow rate was 45 slm, the growth temperature was 480℃, and the growth pressure was 150 torr.

[0061] During the growth of the upper coating layer, the flow rate of NH3 was 60 slm, the growth temperature was 650℃, and the growth pressure was 100 torr. After the growth of the upper coating layer was completed, NH3 was continuously introduced at a flow rate of 60 slm, and the temperature was increased to 1050℃ at a heating rate of 15℃ / min.

[0062] (3) Growing an undoped GaN layer on the buffer layer; Specifically, a three-dimensional island layer and a two-dimensional merged layer were grown sequentially by MOCVD. The growth temperature of the three-dimensional island layer was 1050℃, the growth pressure was 300 torr, and the V / III ratio was 2800. The growth temperature of the two-dimensional merged layer was 1120℃, the growth pressure was 180 torr, and the V / III ratio was 400.

[0063] (4) Growing an N-type GaN layer on an undoped GaN layer; Specifically, an N-type GaN layer was grown by MOCVD at a growth temperature of 1080℃ and a growth pressure of 200 torr.

[0064] (5) Growing an N-type AlGaN layer on an N-type GaN layer; Specifically, an N-type AlGaN layer was grown by MOCVD at a growth temperature of 1020℃ and a growth pressure of 200 torr.

[0065] (6) An active layer is grown on an N-type AlGaN layer; Specifically, quantum well layers and quantum barrier layers are periodically grown using MOCVD until the active layer is obtained. The quantum well layer is grown at a temperature of 780°C and a growth pressure of 200 torr. The quantum barrier layer is grown at a temperature of 880°C and a growth pressure of 200 torr.

[0066] (7) Grow an electron blocking layer on the active layer; Specifically, a p-type AlGaN layer was grown by MOCVD as an electron blocking layer; the growth temperature was 950℃ and the growth pressure was 150 torr.

[0067] (8) Growing a P-type GaN layer on an electron blocking layer; Specifically, a P-type GaN layer was grown by MOCVD at a growth temperature of 970℃ and a growth pressure of 200 torr.

[0068] (9) Growing a contact layer on a p-type GaN layer; Specifically, Mg-doped GaN was grown by MOCVD as a contact layer at a growth temperature of 860℃ and a growth pressure of 200 torr.

[0069] (10) Anneal at 750°C for 10 min in N2 atmosphere.

[0070] Example 2 This embodiment provides a GaN-based LED epitaxial structure, which differs from Embodiment 1 in that: The lower cladding layer is an AlN layer with a thickness of 6 nm. The Zn3N2 layer has a thickness of 25 nm. The upper cladding layer is a GaN layer with a thickness of 12 nm. Accordingly, the MO source is adjusted in the fabrication steps of the upper and lower cladding layers.

[0071] Everything else is the same as in Example 1.

[0072] Example 3 This embodiment provides a GaN-based LED epitaxial structure, which differs from Embodiment 2 in that: In step (2), the growth temperature of the lower coating layer, the Zn3N2 layer, and the upper coating layer is 500℃, and the growth pressure is 100 torr.

[0073] Everything else is the same as in Example 2.

[0074] Example 4 This embodiment provides a GaN-based LED epitaxial structure, which differs from Embodiment 3 in that: In step (2), after the upper coating layer is grown, NH3 with a flow rate of 55 slm is continuously introduced and the temperature is raised to 1050℃ at a heating rate of 15℃ / min, and then isothermal annealing is performed for 5 min.

[0075] Everything else is the same as in Example 3.

[0076] Comparative Example 1 This comparative example provides a GaN-based LED epitaxial structure, which differs from Example 1 in that: The buffer layer is an AlN layer, which is grown by PVD at a growth temperature of 620℃, a sputtering power of 4.5kW, an Ar flow rate of 42sccm, and an O2 flow rate of 8sccm.

[0077] Everything else is the same as in Example 1.

[0078] Comparative Example 2 This comparative example provides a GaN-based LED epitaxial structure, which differs from Example 1 in that: The buffer layer does not include the lower coating layer. Accordingly, the preparation method does not include the step of preparing this layer.

[0079] Everything else is the same as in Example 1.

[0080] Comparative Example 3 This comparative example provides a GaN-based LED epitaxial structure, which differs from Example 1 in that: The buffer layer does not include a Zn3N2 layer. Accordingly, the preparation method does not include a step for preparing this layer.

[0081] Everything else is the same as in Example 1.

[0082] Comparative Example 4 This comparative example provides a GaN-based LED epitaxial structure, which differs from Example 1 in that: The buffer layer does not include an upper coating layer. Accordingly, the preparation method does not include the step of preparing this layer.

[0083] Everything else is the same as in Example 1.

[0084] Comparative Example 5 This comparative example provides a GaN-based LED epitaxial structure, which differs from Example 1 in that: The buffer layer does not include the lower coating layer and the Zn3N2 layer. Accordingly, the preparation method does not include the step of preparing these two layers.

[0085] Everything else is the same as in Example 1.

[0086] Comparative Example 6 This comparative example provides a GaN-based LED epitaxial structure, which differs from Example 1 in that: The buffer layer does not include the Zn3N2 layer and the upper coating layer. Accordingly, the preparation method does not include the step of preparing these two layers.

[0087] Everything else is the same as in Example 1.

[0088] Comparative Example 7 This comparative example provides a GaN-based LED epitaxial structure, which differs from Example 1 in that: The buffer layer does not include a lower coating layer and an upper coating layer. Accordingly, the preparation method does not include the step of preparing these two layers.

[0089] Everything else is the same as in Example 1.

[0090] Comparative Example 8 This comparative example provides a GaN-based LED epitaxial structure, which differs from Example 1 in that: The buffer layer is not included. Accordingly, the preparation method does not include the step of preparing this layer.

[0091] Everything else is the same as in Example 1.

[0092] The GaN-based LED epitaxial structures obtained in Examples 1-4 and Comparative Examples 1-8 were tested (ICP etching to the N-type GaN layer, and AFM testing of the penetration dislocation density). These structures were then fabricated into chips with a vertical structure of 5 mil × 7 mil, and their luminous intensity was measured at 120 mA. Using the data from Comparative Example 1 as a benchmark, the brightness improvement rate of each example and comparative example was calculated. Specific results are shown in the table below:

[0093] As can be seen from the table, the introduction of the buffer layer structure in this invention can effectively reduce the dislocation density of the GaN-based LED epitaxial structure and improve its luminous efficiency. Meanwhile, a comparison of Examples 1 and 2 shows that when AlN (lower cladding layer) / GaN (upper cladding layer) is used to coat the Zn3N2 layer, the dislocation density can be reduced more significantly, and the brightness can be improved. A comparison of Examples 2 and 3 shows that when the lower cladding layer, Zn3N2 layer, and upper cladding layer are grown under the same temperature and pressure conditions, the dislocation density is lower and the brightness is higher, indicating that growth under the same temperature and pressure conditions is beneficial for the protection of the Zn3N2 layer. A comparison of Examples 3 and 4 shows that annealing the upper cladding layer can achieve a lower dislocation density and higher brightness. This is because annealing promotes better GaN nucleation, thus better utilizing the high nucleation density advantage of the Zn3N2 layer.

[0094] A comparison of Example 1 with Comparative Examples 2 to 8 shows that when any one, any two, or the entire buffer layer of the present invention is removed, the dislocation density increases significantly and the brightness decreases. This indicates that the lower coating layer, the Zn3N2 layer, and the upper coating layer in the present invention have a synergistic effect.

[0095] The above description is a preferred embodiment of the invention. It should be noted that, for those skilled in the art, several improvements and modifications can be made without departing from the principle of the invention, and these improvements and modifications are also considered to be within the scope of protection of the invention.

Claims

1. A GaN-based LED epitaxial structure, characterized in that, It includes a substrate, and a buffer layer, an N-type GaN layer, an active layer and a P-type GaN layer are sequentially stacked on the substrate; The buffer layer includes a lower cladding layer, a Zn3N2 layer and an upper cladding layer stacked sequentially on the substrate. The lower cladding layer and the upper cladding layer cover the Zn3N2 layer, so that it has no directly exposed interface. The lower cladding layer is an AlN layer and / or a first AlGaN layer, and the upper cladding layer is a GaN layer and / or a second AlGaN layer.

2. The GaN-based LED epitaxial structure as described in claim 1, characterized in that, The thickness of the lower coating layer is 2nm~15nm, the thickness of the Zn3N2 layer is 10nm~50nm, and the thickness of the upper coating layer is 5nm~20nm.

3. The GaN-based LED epitaxial structure as described in claim 1 or 2, characterized in that, The lower cladding layer is an AlN layer, and the upper cladding layer is a GaN layer.

4. The GaN-based LED epitaxial structure as described in claim 1, characterized in that, The substrate is a silicon substrate or a sapphire substrate.

5. The GaN-based LED epitaxial structure as described in claim 1, characterized in that, The thickness of the N-type GaN layer is 2μm~4μm, and the Si doping concentration is 5×10⁻⁶. 18 cm -3 ~2×10 19 cm -3 ; The active layer comprises alternating layers of quantum wells and quantum barriers with a period number of 5 to 15. The quantum well layer is an InGaN layer with a thickness of 2 nm to 4 nm and an In content of 0.1 to 0.22%. The quantum barrier layer is a GaN barrier layer or an AlGaN barrier layer. The GaN barrier layer has a thickness of 10 nm to 16 nm, and the AlGaN barrier layer has a thickness of 8 nm to 12 nm and an Al content of 0.05 to 0.15%. The thickness of the p-type GaN layer is 100 nm to 200 nm, and its Mg doping concentration is 1 × 10⁻⁶. 19 cm -3 ~5×10 19 cm -3 .

6. The GaN-based LED epitaxial structure as described in claim 1, characterized in that, It also includes undoped GaN layers, N-type AlGaN layers, electron blocking layers, and contact layers; The undoped GaN layer is disposed between the buffer layer and the N-type GaN layer, and its thickness is 2μm~4μm; The N-type AlGaN layer is disposed between the N-type GaN layer and the active layer, with a thickness of 100 nm to 200 nm, an Al composition ratio of 0.1% to 0.2%, and a Si doping concentration of 2 × 10⁻⁶. 18 cm -3 ~5×10 18 cm -3 ; The electron blocking layer is disposed between the active layer and the p-type GaN layer. It is a p-type AlGaN layer with a thickness of 5 nm to 25 nm, an Al content of 0.05 to 0.25%, and a Mg doping concentration of 1 × 10⁻⁶. 18 cm -3 ~5×10 19 cm -3 ; The contact layer is disposed on the p-type GaN layer, and it is a Mg-doped GaN layer with a thickness of 10 nm to 30 nm and a Mg doping concentration of 5 × 10⁻⁶. 19 cm -3 ~5×10 20 cm -3 .

7. A method for preparing a GaN-based LED epitaxial structure, used to prepare the GaN-based LED epitaxial structure as described in any one of claims 1 to 6, characterized in that, include: Provide substrate; A buffer layer, an N-type GaN layer, an active layer, and a P-type GaN layer are sequentially grown on the substrate. The buffer layer comprises a lower cladding layer, a Zn3N2 layer, and an upper cladding layer sequentially stacked on the substrate. The lower cladding layer and the upper cladding layer cover the Zn3N2 layer, so that there is no directly exposed interface. The growth temperature of the buffer layer is 400℃~700℃. The lower cladding layer is an AlN layer and / or a first AlGaN layer, and the upper cladding layer is a GaN layer and / or a second AlGaN layer.

8. The method for preparing a GaN-based LED epitaxial structure as described in claim 7, characterized in that, The growth temperature of the lower coating layer is 400℃~600℃, and the growth pressure is 50 torr~200 torr; and before growing the lower coating layer, the substrate is treated with NH3 or N2 to establish a nitrogen-saturated interface. The growth temperature of the Zn3N2 layer is 400℃~600℃, and the growth pressure is 50 torr~200 torr; the growth temperature of the upper coating layer is 400℃~600℃, and the growth pressure is 50 torr~200 torr. After the upper coating layer is grown, it is annealed in an NH3 atmosphere at 1000℃~1150℃ for 3min~10min. Furthermore, the growth temperature and growth pressure of the lower coating layer, the Zn3N2 layer, and the upper coating layer are the same.

9. The method for preparing a GaN-based LED epitaxial structure as described in claim 7, characterized in that, The flow rate of NH3 during the growth of the buffer layer is 40 slm to 60 slm. After the buffer layer has grown, NH3 is introduced during the heating process at a flow rate of 40 slm to 60 slm.

10. A GaN-based LED, characterized in that, Including the GaN-based LED epitaxial structure as described in any one of claims 1 to 6.